Association of signaling transducers and activators of transcription 1 and systemic lupus erythematosus. (May 2014) - Liang, Yan; Xu, Wang-Dong; Yang, Xiao-Ke; Fang, Xin-Yu; Liu, Yan-Yan; Ni, Jing; Qiu, Li-Juan; Hui, Peng; Cen, Han; Leng, Rui-Xue; Pan, Hai-Feng; Ye, Dong-Qing
Abstract Systemic lupus erythematosus (SLE) is complex autoimmune disease which involves various facets of the immune system. Signaling transducers and activators of transcription 1 (STAT1) belongs to the family of STAT transcription factors that mediate various biological responses. Recently, studies in both experimental animal models of lupus and patients with SLE have revealed expression and activation of STAT1 is closely associated with the pathogenesis of SLE. Moreover, increased production of interferons (IFNs) and aberrant activation of IFNs signaling, which is mechanistically linked to increased level of STAT1, are crucial for the development of SLE. Therefore, we will focus on the association of STAT1 and SLE based on recent understandings to render more information about the mechanisms of STAT1 might perform in. Hopefully, the information obtained will lead to a better understanding of the development and pathogenesis of systemic autoimmune diseases, as well as its clinical implications and therapeutic potential.